Patterns of Alcohol Intake of Pregnant and Lactating Women in Rural Western Australia - Tearne, E.; Cox, K.; Giglia, Roslyn (Springer New York LLC, 2017)
© 2017, Springer Science+Business Media, LLC. Objectives Monitoring surveys and research outline a paucity of alcohol consumption data for women in the period of lactation, particularly in rural areas of developed countries. Identifying the drinking profile of ante- and postnatal women in this population will aid in the effective dissemination of public health interventions. This paper will present the first alcohol consumption data of pregnant and breastfeeding women living in rural Western Australia (WA). Methods A prospective cohort of 489 mothers and their infants were recruited between April 2010 and November 2011. All women regardless of their infant feeding method were followed up at 4, 10, 16, 26, 32, 40 and 52 weeks postpartum. Data were analysed to ascertain the prevalence and patterns of alcohol consumption during pregnancy and lactation. Results Approximately 20% of women consumed alcohol during pregnancy, with a predominance of women from older age groups and smokers. At 4, 6 and 12 months postpartum; 45.9%, 47.0% and 51.9% of breastfeeding mothers were consuming alcohol respectively. Conclusions for Practice There remains a considerable proportion of women who continue to drink during pregnancy. Although proven successful, public health campaigns now need to target women who are older and who smoke. Women are continuing to consume alcohol during the period of lactation, with the majority doing so at low levels.